2020
DOI: 10.1055/s-0040-1715454
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasminogen Concentration at Admission in Patients with Coronavirus Disease 2019 (COVID-19)

Abstract: Letter to the Editor 859 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…25 C3a/C3 was inversely correlated with plasminogen, in agreement with reports of lower plasminogen levels in COVID-19 patients requiring ICU admission, and thus suggesting fibrinolytic system disruption occurring in concert with complement hyperactivation. 26 Fibrinolysis disturbance due to increased PAI-1, 1 however, did not appear to be linked to complement hyperactivity, therefore suggesting that plasminogen depletion may be the result of consumptive fibrinolysis. 28 This association may explain in part the high complement levels observed in COVID-19 patients, given that the microthrombotic process triggered by ADAMTS13 deficiency has been shown to activate complement.…”
Section: Discussionmentioning
confidence: 96%
“…25 C3a/C3 was inversely correlated with plasminogen, in agreement with reports of lower plasminogen levels in COVID-19 patients requiring ICU admission, and thus suggesting fibrinolytic system disruption occurring in concert with complement hyperactivation. 26 Fibrinolysis disturbance due to increased PAI-1, 1 however, did not appear to be linked to complement hyperactivity, therefore suggesting that plasminogen depletion may be the result of consumptive fibrinolysis. 28 This association may explain in part the high complement levels observed in COVID-19 patients, given that the microthrombotic process triggered by ADAMTS13 deficiency has been shown to activate complement.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by the "fibrinolysis resistance" or "fibrinolysis shutdown" in vitro whole blood clot lysis 22,69,70 . The moderate reduction in circulating plasminogen of ICU COVID-19 patients eliminates the thrombolytic effects of tPA 71 , which is supported by thromboelastometry (TEM) 49,72 . As the half-life of plasminogen is 2.2 days, the fibrinolysis resistance in vitro cannot be explained by the distance to the clots in vivo (about 45 seconds per cycle through the circulation system) and the time between collection of blood to assay.…”
Section: Clinicopathological Mechanisms Of Fibrinolysis In Covid-19mentioning
confidence: 89%
“…This discrepancy can, however, be attributed to temporal changes in levels of tPA and PAI-1, as well as to insufficient hyperfibrinolysis characterized by systemic suppression and local (i.e., within the pulmonary tissue) hyperactive fibrinolysis derangement, as recently pinpointed by Ji et al 23 This is in concordance with recent observations by Henry et al where COVID-19 patients progressing to severe disease had lower levels of plasminogen compared with discharged patients. 12 This suggests that the high D-dimer levels observed in patients with severe COVID-19 may come from an initial rise in tPA/plasmin. This hypothesis is further supported by observations by Wright and colleagues where patients who met the criteria of hypofibrinolysis based on thromboelastographic findings had a marked decline in D-dimer levels after an initial rise.…”
mentioning
confidence: 99%
“…11 Henry and colleagues recently demonstrated that ICU-admitted COVID-19 patients had lower levels of circulating plasminogen than non-ICU patients, suggesting an exhaustion of fibrinolysis. 12 Recent small clinical studies have also demonstrated potential therapeutic effects of supplementing the fibrinolytic system, where exogenous administration of tissue plasminogen activator (tPA) resulted in improvement of respiratory function and reduced mortality in critically ill COVID-19 patients with acute respiratory distress syndrome (ARDS). 13,14 Herein, we performed a prospective observational study to determine whether circulating plasma levels of plasminogen activator inhibitor-1 (PAI-1) and tPA may be significantly elevated in patients with severe COVID-19.…”
mentioning
confidence: 99%